2021
DOI: 10.1038/s41598-021-85227-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Safety and efficacy of favipiravir versus hydroxychloroquine in management of COVID-19: A randomised controlled trial

Abstract: Favipiravir is considered a potential treatment for COVID-19 due its efficacy against different viral infections. We aimed to explore the safety and efficacy of favipiravir in treatment of COVID-19 mild and moderate cases. It was randomized-controlled open-label interventional phase 3 clinical trial [NCT04349241]. 100 patients were recruited from 18th April till 18th May. 50 patients received favipiravir 3200 mg at day 1 followed by 600 mg twice (day 2–day 10). 50 patients received hydroxychloroquine 800 mg at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 26 publications
0
38
1
Order By: Relevance
“…Risk of bias assessment of the included studies was reported in Table 1. Among the randomized studies, one study [7] has low risk, six studies [8][9][10][11][12][13][14] have moderate risk, and two studies [15,16] have high risk. Observational studies [14,17] are identified as moderate risk, and nonrandomized study [18] is found to have serious risk.…”
Section: Overview Of Randomized Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk of bias assessment of the included studies was reported in Table 1. Among the randomized studies, one study [7] has low risk, six studies [8][9][10][11][12][13][14] have moderate risk, and two studies [15,16] have high risk. Observational studies [14,17] are identified as moderate risk, and nonrandomized study [18] is found to have serious risk.…”
Section: Overview Of Randomized Resultsmentioning
confidence: 99%
“…Three trials compared Favipiravir with standard supportive care and one of these administered other antiviral medications outside of Favipiravir [14,16,17]. Three trials compared Favipiravir with Hydroxychloroquine [7,9,13], one compared with Chloroquine [12], two compared with Lopinavir/Ritonavir [10,18], and one compared with Umifenovir (Arbidol) [15]. Favipiravir was used in varying doses (Table 2).…”
Section: Overview Of Randomized Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Favipiravir is an approved drug for treating in uenza and has been found associated with SARS-CoV-2 clearance if treated early [34]. Favipiravir has been effective for mild and moderate patients, albeit clinical trials are going on for more clinical evidence in favor of the drug [34,43].…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine Chloroquine is a malaria drug, which passively diffuses into acidic lysosomes, endosomes, and Golgi vesicles. While initial reports and studies were promising for chloroquine/hydroxychloroquine in COVID-19 patients, these findings were not confirmed and the NIH discontinued clinical trials investigating the efficiency of chloroquine (3,97). In 2020, the FDA had authorized the administration of chloroquine to certain COVID-19 patients, but shortly thereafter, the agency terminated its use due to the high ambiguity regarding its efficiency and side effects (Table 4).…”
Section: Drugs and Vaccines Drugsmentioning
confidence: 99%